2021
DOI: 10.1186/s12877-021-02009-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of reduced retinal arteriolar tortuosity with depression in older participants from the Northern Ireland Cohort for the Longitudinal Study of Ageing

Abstract: Introduction The retina shares similar anatomical and physiological features with the brain and subtle variations in retinal microvascular parameters (RMPs) may reflect similar vascular variation in the brain. The aim of this study was to assess associations between RMPs and measures of depression in the Northern Ireland Cohort for the Longitudinal Study of Ageing. Methods RMPs (arteriolar and venular caliber, fractal dimension and tortuosity) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…In individuals with T2DM and depression, wider arteriolar width in the retina has been observed [ 125 ]. Table 1 highlights associations between a wider retinal venular or arteriolar calibre, reduced arterial tortuosity, and higher plasma markers of endothelial dysfunction with an increased prevalence or incidence of depression [ 122 , 126 , 127 , 128 , 129 ]. However, inconsistencies in reporting this association exist, potentially attributable to selection bias, variations in retinal microvascular changes, and differences in measurement time points [ 130 , 131 ].…”
Section: Depression and Retinal Microvascular Changesmentioning
confidence: 99%
“…In individuals with T2DM and depression, wider arteriolar width in the retina has been observed [ 125 ]. Table 1 highlights associations between a wider retinal venular or arteriolar calibre, reduced arterial tortuosity, and higher plasma markers of endothelial dysfunction with an increased prevalence or incidence of depression [ 122 , 126 , 127 , 128 , 129 ]. However, inconsistencies in reporting this association exist, potentially attributable to selection bias, variations in retinal microvascular changes, and differences in measurement time points [ 130 , 131 ].…”
Section: Depression and Retinal Microvascular Changesmentioning
confidence: 99%
“…Building on research showing that psychosocial stress in childhood was associated with cardiovascular dysfunction, some studies have investigated the effects of psychosocial stress on the retinal microvasculature. Altered retinal microvasculature has been associated with depression and anxiety in adolescents and adults (56)(57)(58)(59)(60)(61), lower quality of life (62), and vital exhaustion (63). However, some studies have found either a weak association or no association between psychosocial stress and retinal microvasculature (64,65).…”
Section: The Retina As a Model Of Brain Healthmentioning
confidence: 99%
“…So depression in the elderly is a chronic disease that needs urgent attention. 4 Depression is a intricate public health problem with the characteristics of large differences in response to treatment.The systemic complexity of depression, or the feedback process between the different drivers of the disorder, leads to the persistence of depression. 5 According to reports, systemic chronic low-grade inflammation is related to the progression of Major depressive disorder (MDD) by affecting monoaminergic and glutamatergic neurotransmission.However, whether various proinflammatory cytokines are abnormally elevated before the first onset of depression remains unclear.…”
Section: Introductionmentioning
confidence: 99%